2023
DOI: 10.1039/d3fd00022b
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the capabilities of bipolar conical channels in neuromorphic iontronics

Abstract: We quantitatively explain the diodic and memristive properties of conical ion channels with bipolar surface charges. A modelled iontronic circuit of these channels exhibits neuronal spiking with membrane potentials comparable to mammalian values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…In this work we expand upon the previously reported features of neuronal spiking in fluidic iontronics [15,29]. By building upon a previously reported iontronic circuit [15] and a physical description of the dynamical conductance of conical channels with a bipolar (BP) surface charge [39], i.e. positive at the base and negative at the tip, we can unlock various new forms of spiking dynamics.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…In this work we expand upon the previously reported features of neuronal spiking in fluidic iontronics [15,29]. By building upon a previously reported iontronic circuit [15] and a physical description of the dynamical conductance of conical channels with a bipolar (BP) surface charge [39], i.e. positive at the base and negative at the tip, we can unlock various new forms of spiking dynamics.…”
Section: Introductionmentioning
confidence: 83%
“…Conical fluidic ion channels act as iontronic volatile memristors [40] and are being investigated as possible candidates for synaptic devices [41] and spiking circuits [15,39]. Using theoretical models that quantitatively explain the memristive behaviour of conical channels, it was shown that HH-inspired fluidic circuits containing three conical channels and a capacitor exhibit tonic and phasic spiking [15,39].…”
Section: Iontronic Circuit and Bp Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ion-based neuromorphic devices have attracted wide interest both in fundamental and applied chemistry audiences. The basic building block of neuromorphic signal processing is the memristor. Here, we describe a multipore nanofluidic memristor with conical pores on a polymeric substrate that shows a wide range of ionic conduction properties, including current rectification. This electrochemical memory resistor exhibits a robust history-dependent behavior based on the electrical interaction between the functionalized charges on the conical pore surface and the nanoconfined ionic solution. We show that the memristor active response can be switched in current and polarity by pH control, which provides additional functionality for chemical computation and neuromorphic applications.…”
mentioning
confidence: 99%